Hubungan migrasi perlekatan otot pada tulang panjang dengan perubahan panjang tulang dan volume otot pada perlakuan hiperaktivitas selama pertumbuhan - Boer, H. Ardiyan (Jurnal Kedokteran YARSI, 2009)
This study was aimed to recognize the ccorrelation between migration of muscle attachment on long bone and the change of bone length and mucle volume in a hyperactivity treatment during bone growth. A number of 150 male rats (Rattus norvegicus) were used as experimental animal. Randomly, the experimental animals were divided into three groups (1) the first group consisted of 30 rats, were used to examine the anatomical structure of the rats, and the accuracy of placing metal pins of muscles and of the bone shaft, (2) the control group (60 rats) and (3) the hyperactivity group (60 rats) were given increased muscular activity by physical exercise in every groups. Metal pins were implanted in the middle of the femoral and the tibial bone shaft, and 30 rats (the first group) were directly sacrificed. Every 2 months and 6 months following treatment, the hyperactivity and the control group were sacrificed. Five muscles which were attached on the femur and on the tibia were cut and their volumes, absolute distance and proportional distance of their attachment to the metal pins, and to the length of the bone were measured. It was found that in the hyperactivity rats, a change of bone length was detected, whereas none in the control group. The change of the long bone was significantly correlated proportionally with the migration of the attachment of the muscle. In the treated group, muscle volume differed compared to that in the control group. However, the difference of the muscle volume was not correlated with the migration of the muscle attachment during bone growth. In conclusion, there was a convincing correlation between the migration of the muscle attachment and the change of bone length in hyperactivity group during bones growth.